EVALUATION OF COMPUTER LABORATORY SPACE DURING THE COVID-19 PANDEMIC AT SMK NEGERI 7 BALEENDAH - Puspita Alfira Nareswari; Asep Yudi Permana; Nitih Indra Komala Dewi (Universitas Pendidikan Indonesia, 2022)
Abstract - This study aims to obtain an overview of the condition and availability of facilities and infrastructure for the computer laboratory room for the Modeling and Building Information Design (DPIB) program at SMK Negeri 7 Baleendah based on Permendikbud No. standards. 34 of 2018. The purpose of this study was also to assess the fulfillment of health protocol facilities at SMK Negeri 7 Baleendah and to obtain a computer laboratory layout plan that complies with health protocol rules during the Covid-19 pandemic. This research is an evaluation research. Data collection techniques in this study by means of observation and documentation. The results of this study indicate the level of achievement of facilities and infrastructure at SMK Negeri 7 Baleendah based on Permendikbud No. standards. 34 of 2018 it reached 83% in computer laboratory room infrastructure, its achievement was included in the very feasible criteria and in the facilities it reached 72.91% which was included in the feasible criteria. The results of the evaluation on health protocol facilities based on existing standards had not been fulfilled, the sink near the computer laboratory room did not provide hand washing soap, and the layout of the computer laboratory room had not been spaced 1.5 meters apart. Design recommendations for the computer laboratory room for the DPIB program at SMK Negeri 7 Baleendah by changing the type of opening, the position of the sink placed next to the entrance to the computer laboratory room and the room layout spaced 1.5 meters apart on each seat. The results of the evaluation on health protocol facilities based on existing standards had not been fulfilled, the sink near the computer laboratory room did not provide hand washing soap, and the layout of the computer laboratory room had not been spaced 1.5 meters apart. Design recommendations for the computer laboratory room for the DPIB program at SMK Negeri 7 Baleendah by changing the type of opening, the position of the sink placed next to the entrance to the computer laboratory room and the room layout spaced 1.5 meters apart on each seat. The results of the evaluation on health protocol facilities based on existing standards had not been fulfilled, the sink near the computer laboratory room did not provide hand washing soap, and the layout of the computer laboratory room had not been spaced 1.5 meters apart. Design recommendations for the computer laboratory room for the DPIB program at SMK Negeri 7 Baleendah by changing the type of opening, the position of the sink placed next to the entrance to the computer laboratory room and the room layout spaced 1.5 meters apart on each seat. Keywords– Computer Laboratories, Facilities and Infrastructure, Health Protocol Facilities, Standard Computer Laboratory Facilities